Whole-school collaboration for social skill development in character education - R. Rafiqah; Iis Siti Aisyah; Agus Tinus; Peter Adewale (Universitas Muhammadiyah Malang, 2025)
Social skills are pivotal to holistic education, yet character education initiatives in Indonesia are often carried mainly by school counselors. This study examined how a whole-school approach integrating counselors, teachers, and administrators strengthens students' social skills through character education. A sequential explanatory mixed-methods design was used at SMA Negeri 4 Sampit (Central Kalimantan). Interviews, classroom observations, and document review involved the principal, vice principal, counselor, and two subject teachers, followed by a 14-item social-skills questionnaire completed by 183 students (grades X–XII). Qualitative data were analyzed using Miles, Huberman, and Saldaña's interactive model; quantitative data used descriptive statistics. Counselors promoted empathy and reflection through individual counseling; teachers applied role play, restitution triangle, and classroom agreements; administrators supported policies and resources. Overall, 92% of students demonstrated high/very high social skills, with empathy, communication, and cooperation strongest, while conflict resolution and self-management were moderate. Collaborative, role-complementary whole-school character education appears effective, but structured interventions are needed to improve conflict resolution and self-management.